TRANSFORMATION OF HUMAN RESOURCE MANAGEMENT IN EDUCATION IN THE DIGITAL ERA: TRANSFORMASI MANAJEMEN SDM DALAM PENDIDIKAN DI ERA DIGITAL - Saifudin, Moh; Rindanigsih, Ida (Antis-Publisher, 2024)
Education is an important foundation of societal development and managing human resources (HR) is key to the success of educational institutions. This article explores the basic concepts of human resource management (HRM), the role of digital transformation and its relevance in the context of education. Digital transformation has changed the education paradigm, presenting new challenges and unlimited opportunities in HRM. However, in-depth understanding of the integration between HRM and digital transformation in educational contexts is limited. This article aims to investigate the role of digital transformation in educational HRM, outline the basic concepts of HRM, and highlight its relevance in the current educational setting. A desk research method was used to evaluate literature related to HRM, digital transformation, and education. An in-depth review was conducted to present a comprehensive overview of the topic. The concept of HRM in education involves recruitment, development, performance management, and technology integration in the education process. Digital transformation changes the way of interaction, staff development, performance management, and affects the educational paradigm. A good integration between the two creates an educational environment that is adaptive, oriented towards individual development, and responsive to change. The integration of digital transformation with basic HRM concepts is crucial in creating an adaptive educational environment.